Studi geografis tentang pemanfaatan sumber daya air di Kota Malang - Arif, M. Bahaudin (Maliki Interdisciplinary Journal, 2024)
Malang City, a city located in East Java Province, Indonesia, is known for its natural beauty and abundant natural resource potential. One vital natural resource is water, which is used in various aspects of daily life, from agriculture to industry. This study aims to carry out a geographical analysis of the use of water resources in Malang City, with a focus on aspects of distribution, quality and management.